Changes of Expression of Stretch-activated Potassium Channel TREK-1 mRNA and Protein in Hypertrophic Myocardium - 程龙献 苏方成 瑞奔曾哥 樊红 黄恺 王敏 彭红玉 梅春丽 赵芳 廖玉华 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
The expression of stretch activated potassium channel TREK-1 mRNA and protein of hypertrophic myocardium was measured. Using a model of hypertrophy induced by coarctation of abdominal aorta in male Wistar rats, the expression of TREK-1 mRNA and protein was detected by using semi quantitative RT-PCR and Western blot respectively. At 4th and 8th week after constriction of the abdominal aorta , rats developed significant left ventricular hypertrophy. As compared to sham-operated group, stretch-activated potassium channel TREK-1 mRNA was strongly expressed and protein was up regulated in operation groups （P〈0.05）. It was concluded that the expression of TREK-1 was up-regulated in hypertrophic myocardium induced by chronic pressure overload in Wistar rats.